Суб’єкти кримінального переслідування у досудовому провадженні та у провадженні в суді першої інстанції - Маілунц, Белла Еріківна; Маилунц, Белла Эриковна; Mailunts, Bella E. (My University, 2019)
Дисертація на здобуття наукового ступеня кандидата юридичних наук за спеціальністю 12.00.09 – кримінальний процес та криміналістика; судова експертиза; оперативно-розшукова діяльність. – Національний університет «Одеська юридична академія», Одеса, 2019. Дисертація є першим після прийняття КПК України 2012 року спеціальним комплексним дослідженням теоретичних та практичних проблем визначення процесуального статусу та компетенції суб’єктів кримінального переслідування в досудовому розслідуванні та в суді першої інстанції. У дисертації досліджено категорію кримінального переслідування, поняття його суб’єктів, їх класифікацію та взаємодію між собою. Охарактеризоване процесуальне становище прокурора як суб’єкта кримінального переслідування, визначено можливість здійснення контролю за прокурором у ході самостійного проведення ним слідчих (розшукових) дій та негласних слідчих (розшукових) дій у досудовому розслідуванні; розкрито особливості процедури повідомлення особі про підозру як один із способів реалізації кримінального переслідування; визначено підстави для зміни обвинувачення прокурором під час судового засідання. Розкрито процесуальні можливості представника та законного представника потерпілого в частині подання доказів в ході кримінального переслідування; з’ясовано особливості процесуального становища потерпілого як суб’єкта кримінального переслідування в судовому засіданні. Виділено та охарактеризовано специфіку процесуального статусу цивільного позивача при реалізації ним кримінального переслідування. У дисертації розроблено теоретичну концепцію суб’єктів кримінального переслідування у досудовому провадженні та в суді першої інстанції, сформульовано науково-практичні рекомендації щодо вдосконалення положень чинного КПК України в частині регламентації їх діяльності.

Диссертация на соискание научной степени кандидата юридических наук по специальности 12.00.09 – уголовный процесс и криминалистика; судебная экспертиза; оперативно-розыскная деятельность. – Национальный университет «Одесская юридическая академия», Одесса, 2019. Диссертация является первым после принятия УПК Украины 2012 года специальным комплексным исследованием теоретических и практических проблем определения процессуального статуса и компетенции субъектов уголовного преследования в досудебном расследовании и в суде первой инстанции. Охарактеризовано процессуальное положение прокурора как субъекта уголовного преследования, определена возможность осуществления контроля за прокурором во время самостоятельного проведения им следственных (розыскных) действий и негласных следственных (розыскных) действий в досудебном расследовании; раскрыты особенности процедуры уведомления лицу о подозрении как один из способов реализации уголовного преследования; определены основания для изменения обвинения прокурором в ходе судебного заседания. Раскрыты процессуальные возможности представителя и законного представителя потерпевшего в части представления доказательств в ходе уголовного преследования; раскрыты особенности процессуального положения потерпевшего как субъекта уголовного преследования в судебном заседании. Выделена и раскрыта специфика процессуального статуса гражданского истца при реализации им уголовного преследования. В диссертации разработана теоретическая концепция субъектов уголовного преследования в досудебном производстве и в суде первой инстанции, сформулированы научно-практические рекомендации по совершенствованию положений действующего УПК Украины в части регламентации их деятельности

The thesis for a Candidate of Law Degree, speciality 12.00.09 – Criminal Process and Criminalistics, Forensic Examination, Operation search activity. – National University «Odessa Law Academy», Odesa, 2019. Dissertation is the first special comprehensive study of theoretical and practical problems of determining the procedural status and competence of subjects of criminal prosecution during the pre-trial investigation and in the court of first instance after the adoption of the CPC of Ukraine in 2012. In the dissertation concepts, legal nature and types of criminal prosecution, concept of subjects of criminal prosecution, their classification and interaction with each other, as well as the peculiarities of participation of all subjects of criminal prosecution during pre-trial investigation, preparatory proceedings and trial were investigated. Subjects of criminal prosecution are defined as participants in criminal proceedings that carry out the function of criminal prosecution, on other words, they carry out activities for the establishment of a specific person who committed a criminal offense and for the disclosure of this person in pre-trial investigation and proving his guilt in court through the exercise of state powers or rights, which they have according to criminal procedural law. Classification is carried out depending on the interest in prosecution, depending on the stages in which they can use their rights and powers within the framework of criminal prosecution and on the basis of initiation of participation in criminal prosecution. It was proved that the head of pre-trial investigation agency was unjustifiably referred in paragraph 19 of Part 1 of Article 3 of the CPC to the prosecution side and can not be recognized as the subject of criminal prosecution. It is substantiated that a civil plaintiff is the subject of criminal prosecution, since: compensation for the victim’s damage depends on whether the person’s guilt in the court has been proved, which is one of the determining elements of the criminal prosecution; the basis of the criminal procedural activity of a civil plaintiff in criminal proceedings is the successful implementation of function of criminal prosecution; while maintaining a civil action, his activity is actually aimed at promoting the function of criminal prosecution in a criminal proceeding; the civil plaintiff, given the specific position in the criminal proceedings, may have evidences that were not known to the investigator and could help to prove the guilty of the suspect (accused), the maintenance of a civil action may significantly affect the course of the whole criminal proceedings and, as a consequence, the prosecution. The author established that among the powers of the prosecutor, which are provided in Part 2 of Art. 36 of the CPC, powers within the framework of criminal prosecution include following: independently initiate a pretrial investigation; personally conduct investigative (search) actions, covert investigative (search) actions; submit an application for investigative (search) actions, covert investigators (searches) to the investigator; notify the person about the suspicion, submit an indictment or a motion to impose compulsory medical measures. An expanded interpretation of Part 1 of Article 291 of the CPC as part of the definition of unlimited list of grounds for drawing up an indictment by the prosecutor was established. It was established that victim’s refusal to prosecute in a criminal proceeding in the form of a private prosecution can be either written or oral. At the same time, such a refusal must in any case be recorded in the materials of criminal proceedings. Therefore, in the event of an oral refusal of the prosecution to the investigator or prosecutor, it is expedient to submit a record of the refusal of victim from the prosecution. In such protocol, in addition to the text of victim’s refusal, the legal consequences of such a refusal must be indicated, and the victim himself must testify in written form that he understand such consequences. If necessary, the investigator or prosecutor must explain to victim what the consequences of refusal of prosecution will be. If the refusal is expressed in written form, victim must make a corresponding application for refusing and submit it to prosecute an investigator or prosecutor. An unified list of victim’s rights, which he can use in the case of prosecution’s self-sustaining in court, is offered. It was established that the civil plaintiff as a subject of criminal prosecution in court has the right: to support or refuse a civil action; to declare drains; to submit evidence for the confirmation of a civil suit; to participate in the study of evidence relating to a civil suit; to participate in the interrogation of the accused, witnesses, and expert on matters relating to civil action; to participate in court debates; to be acquainted and receive a judicial decision that is being settled in a civil suit. In the dissertation author developed the theoretical concept of subjects of criminal prosecution during pre-trial investigation and in the court of first instance, formulated scientific and practical recommendations on the improvement of current CPC of Ukraine in terms of regulation of their activities.
дис. ... канд. юрид. наук: 12.00.09
Маілунц Б.Е. Суб’єкти кримінального переслідування у досудовому провадженні та у провадженні в суді першої інстанції: дис. ... канд. юрид. наук: 12.00.09 / Маілунц Белла Еріківна. - Одеса, 2019. - 230 с.
Keywords: кримінальне переслідування; прокурор; слідчий; оперативні підрозділи; потерпілий; цивільний позивач; досудове розслідування; підготовче провадження; судовий розгляд; уголовное преследование; прокурор; следователь; оперативные подразделения; потерпевший; гражданский истец; досудебное расследование; подготовительное производство; судебное разбирательство; prosecution; prosecutor; investigator; operational units; victim; civil plaintiff; pre-trial investigation; preparatory proceedings; trial